Endoplasmic Reticulum-Shaping Atlastin Proteins Facilitate KSHV Replication - Long, Wen-ying; Zhao, Guo-hua; Wu, Yao (Frontiers in Cellular and Infection Microbiology, 2022)
Kaposi’s sarcoma-associated herpesvirus (KSHV) has two life cycle modes: the latent and lytic phases. The endoplasmic reticulum (ER) is the site for KSHV production. Furthermore, ER stress can trigger reactivation of KSHV. Little is known about the nature of the ER factors that regulate KSHV replication. Atlastin proteins (ATLs which include ATL1, ATL2, and ATL3) are large dynamin-related GTPases that control the structure and the dynamics of the ER membrane. Here, we show that ATLs can regulate KSHV lytic activation and infection. Overexpression of ATLs enhances KSHV lytic activation, whereas ATLs silence inhibits it. Intriguingly, we find that silencing of ATLs impairs the response of cells to ER stress, and ER stress can promote the lytic activation of KSHV. Our study establishes that ATLs plays a critically regulatory role in KSHV infection, thus expanding the known scope of biological processes controlled by ATLs to include KSHV infection.